Anion–π interactions in lithium–organic redox flow batteries. Issue 16 (6th February 2019) - Li, Lei; Hong, Yu-Jian; Chen, Dong-Yang; Xiao, Wang-Chuan; Lin, Mei-Jin
Abstract : The interactions between the electrolyte anions and electron-deficient redox-active organic molecules (anion–π interactions) have strong influences on the battery properties due to the anion–π-induced formation of radical anions or sandwich-like aggregates. Abstract : The anions in electrolytes are the carriers of lithium ions for lithium–organic redox flow batteries. Herein, we reported that the interactions between the electrolyte anions and electron-deficient redox-active organic molecules (anion–π interactions) have strong influences on the battery properties due to the anion–π-induced formation of radical anions or sandwich-like aggregates.